PENGARUH DIKLAT, KOMUNIKASI DAN KEPEMIMPINAN TERHADAP MOTIVASI DAN KINERJA PNS PADA KANTOR REGIONAL VI, VII DAN XII BADAN KEPEGAWAIAN NEGARA - Emel Mayabari; Susi Hendriani; Samsir Samsir (Jurnal Ekonomi, 2017)
This study aimed to analyze the influence of training, communication, andleadership on motivation dan performance of civil servants at Sixth, Seventh AndTwelfth Regional Offices of National Civil Service Agency.The population in this study were civil servants amounted to 240 people. 150 samples were determined by using Slovin formula with concordance rate 5% and taken by stratified sampling method. Data collection technique used questionnaires and interviews. The analysis tool used is SEM using SmartPLS version 2.0.The results of this study indicate that : (1) Training has possitive and significant effect on civil servant’s motivation. (2) Communication has possitive and not significant effect on civil servant’s motivation. (3) Leadership has possitive and significant effect on civil servant’s motivation. (4) Training has possitive and significant effect on civil servant’s performance. (5) Communication has possitive and significant effect on civil servant’s performance. (6) Leadership has possitive and significant effect on civil servant’s performance. (7) Motivation has possitive and significant effect on civil servant’s performance.